Integrated biomaterials for biomedical technology - Ramalingam, Murugan; Tiwari, Ashutosh; Ramakrishna, Seeram; Kobayashi, Hisatoshi (Biomaterials science, engineering and technology, 2012)
"The book provides all the important aspects dealing with the basic science involved in materials in biomedical technology, especially structure and properties, techniques and technological innovations in material processing and characterizations, as well as the applications"--Provided by publisher.